CT manifestations of primary esophageal tuberculosis - Zhong Huang; Shaoyong Zhang; Ruikun Liao; Zhi Wang (BMC Infectious Diseases)
Abstract Background Primary esophageal tuberculosis is an uncommon manifestation of Mycobacterium tuberculosis infection in Asian adults, often presenting with nonspecific symptoms that can complicate diagnosis. This report details a case of primary esophageal tuberculosis in middle age female, emphasizing the diagnostic value of computed tomography (CT) imaging. Case presentation The patient, a 46-year-old female from Sichuan Province, China, experienced recurrent choking and mild retrosternal pain postprandially. She exhibited a weight loss of approximately 1 kg over a week, without additional symptoms such as dysphagia or fever. Esophagoscopy disclosed a small ulcer, and CT imaging revealed esophageal wall thickening with mucosal ulceration. A left thoracic lower and middle esophagectomy was conducted, with postoperative pathology confirming granulomatous inflammation, indicative of tuberculosis. Conclusions This case highlights the pivotal role of CT imaging in diagnosing primary esophageal tuberculosis. The imaging modality’s ability to delineate subtle mucosal ulcerations and wall thickening provides a crucial diagnostic advantage, facilitating accurate and timely diagnosis of this rare condition.